Kenyamanan dan kondisi lingkungan sebagai daya tarik minat kunjung masyarakat di perpustakaan umum kabupaten magetan - Pramesti Aruhia Cahyani; Sekar Gandes Kinanthi (Prosiding Konferensi Ilmiah Dasar, 2026)
A public library plays a strategic role in providing information services and shaping the reading culture of the surrounding community. This study aims to describe the physical condition and comfort of the Magetan Regency Public Library and how these aspects attract public interest in visiting. This research used a qualitative descriptive approach with a case study design. Data were collected through direct field observation and in-depth interviews with library staff, then analyzed descriptively. The results show that the library is well maintained, clean, and has a cool and pleasant atmosphere that supports a comfortable reading experience for visitors. The physical facilities, air circulation, and cleanliness of the building were found to be key factors contributing to visitor comfort. These findings are in line with previous studies indicating that facility quality and interior comfort positively influence the public's interest in visiting a library. This study is expected to contribute to the development of the Magetan Regency Public Library and to serve as a reference for similar library management studies.